ARE JOHN KNUDSEN, KJERSTI G. BERG (ed.) - Continental Encampment. Genealogies of Humanitarian Containment in the Middle East and Europe - Canet, Juana (ZARCH, 2024)
ARE JOHN KNUDSEN, KJERSTI G. BERG (ed.) Continental Encampment. Genealogies of Humanitarian Containment in the Middle East and Europe Bergham Books, New York, Oxford, 2023, 276 pp. Tapa dura. 99,00 £ Idioma: inglés ISBN (Pbk.): 978-1-80073-844-7 eISBN (eBook): 978-1-80073-845-4